IMPLEMENTASI PENANAMAN KESADARAN PENTINGNYA KETERAMPILAN SOFT SKILLS ENTREPRENEURSHIP WADAH PENGEMBANGAN FKIP UNBARI - Masni, Harbeng; Rahima, Ade; Hutabarat, Zuhri Saputra (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Implementation of Instilling Awareness of the Importance of Soft Skills Entrepreneurship Through Student Development FKIP UNBARI